Personal Exposure and Indoor Home Particulate Matter: A Review - M. Mohammadyan (Iranica Journal of Energy and Environment, 2012)
This review deals with field studies of particles indoors and exposure to particulate concentrations on recent surveys of homes. The results of indoor and personal exposure concentrations are presented. In addition the effect of other related air pollution factors which might have an effect on exposure to particles are discussed. This paper surveys of particle concentrations and sources in homes from 1981 to 2011. Three major studies which in the USA and a large scale study in Europe that carried out to measure personal exposure and indoor home particle concentrations. A number of small personal exposure studies in homes are also briefly summarized. Personal exposure studies in the USA, EXPOLIS cities and Toronto, and others similar studies have documented that the personal exposure to PM2.5 concentrations was higher than those measured indoors. Most of these studies found a suitable relationship between residential indoor and personal exposure to particulate matter. Personal exposure to respirable particulate matter highly correlated with indoor air. Ambient concentrations obtained from Fixed Site Monitors poorly correlated with total personal exposure to particulate matter concentrations. Some indoor particle source such as smoking, cooking and resuspension of indoor dust may increase subjected to personal exposure and indoor particulate concentrations.